2019
DOI: 10.22441/mix.2019.v9i3.001
|View full text |Cite
|
Sign up to set email alerts
|

CUSTOMER LOYALTY FROM PERSPECTIVE OF MARKETING MIX STRATEGY AND CUSTOMER SATISFACTION A study from Grab - Online Transportation in Era of Industrial Revolution 4.0

Abstract: ABSTRACT. This study aims to examine and analyze the influence of marketing mix 7P (product, price, promotion, place, people, physical evidence, and process) on costumer loyalty with the mediating role of customer satisfaction. A lesson from case of overlapping online transportation user base in Indonesia, specificly from Grab’s Consumer perspective. The research was design by using conclusive experiment, in casual type, with quantitative and survey methods. The sampling method used is sampling judgmental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
3
0
4
Order By: Relevance
“…It can be concluded that if Loodst Coffee and Kopi Budaya Cafe want to increase customer satisfaction, it is very important for Loodst Coffee and Kopi Budaya Cafe to pay attention to pricing that can compete with other similar competitors. The results of the study are in line with research conducted by (Surya, 2019) and (Muzakki, 2019) which prove that price affects customer satisfaction. In contrast to research (Dhuhita, 2017) which states that price has no effect on customer satisfaction.…”
Section: The Effect Of Price Satisfactionsupporting
confidence: 88%
“…It can be concluded that if Loodst Coffee and Kopi Budaya Cafe want to increase customer satisfaction, it is very important for Loodst Coffee and Kopi Budaya Cafe to pay attention to pricing that can compete with other similar competitors. The results of the study are in line with research conducted by (Surya, 2019) and (Muzakki, 2019) which prove that price affects customer satisfaction. In contrast to research (Dhuhita, 2017) which states that price has no effect on customer satisfaction.…”
Section: The Effect Of Price Satisfactionsupporting
confidence: 88%
“…Then, Perceived Price has potential for influencing customer's decision to use brand (Kotler & Keller, 2016:488). Perception consumers on price will influence customer to be loyal in using online transportation service if customers already have been satisfied (Surya, 2019 andSaputri, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian sebelumnya yang telah dilakukan Daryanto & Hasiholan, Setyani & Prabowo (2020) dan R. H. Perdiana (2021) dampak yang kuat dan menguntungkan pada peningkatan penjualan. Dalam penyelidikan sebelumnya yang telah dilakukan oleh Mariska & Sitanggang (2021) dan A. P. Surya (2019) tidak berpengaruh signifikan terhadap peningkatan penjualan Tempat adalah bagian dari bauran pemasaran karena mempengaruhi bagaimana produk didistribusikan dari produsen ke pelanggan. Namun, "tempat" dapat dipahami dalam arti yang lebih luas dari sekedar lokasi fisik operasi perusahaan.…”
Section: Pendahuluanunclassified